2016
DOI: 10.1002/pssr.201600189
|View full text |Cite
|
Sign up to set email alerts
|

Polarity control and residual strain in ZnO epilayers grown by molecular beam epitaxy on (0001) GaN/sapphire

Abstract: We report on the polarity control of ZnO grown by plasma assisted molecular beam epitaxy on Ga polar (0001) GaN/sapphire templates simply via the oxygen‐to‐Zn (VI/II) ratio during the growth of a thin nucleation layer at 300 °C. Following Zn pre‐exposure, the ZnO layers nucleated with low VI/II ratios (<1.5) exhibited Zn‐polarity. Those nucleated with VI/II ratios above 1.5, exhibited O‐polarity. Supported by scanning transmission electron microscopic imaging, we have unequivocally demonstrated that polarity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Single-crystalline ZnO thin films were grown on GaN(0001)/ c-sapphire templates following the methods previously reported. 16 Briefly, Ga-polar (0001) GaN was deposited onto c-plane sapphire by metal-organic chemical vapor deposition. After cleaning in aqua regia and aqueous HCl in order to remove potential metal contamination, the GaN templates were loaded into a plasma enhanced molecular beam epitaxy (PE-MBE) system wherein the GaN surface was further thermally cleaned followed by exposure to a Zn beam.…”
Section: Growth Of Zno Thin Filmsmentioning
confidence: 99%
“…Single-crystalline ZnO thin films were grown on GaN(0001)/ c-sapphire templates following the methods previously reported. 16 Briefly, Ga-polar (0001) GaN was deposited onto c-plane sapphire by metal-organic chemical vapor deposition. After cleaning in aqua regia and aqueous HCl in order to remove potential metal contamination, the GaN templates were loaded into a plasma enhanced molecular beam epitaxy (PE-MBE) system wherein the GaN surface was further thermally cleaned followed by exposure to a Zn beam.…”
Section: Growth Of Zno Thin Filmsmentioning
confidence: 99%
“…Note that the broadening of the reflection from Be 0.02 Mg 0.26 ZnO is due to its thinness. The tensile biaxial strain in the ZnO layer is an indication of the Zn-polar heterostructure, as investigated in our previous study 13 . Be and Mg contents in the BeMgZnO quaternary were calculated from the Bragg angle of its XRD (0002) reflection and emission photon energy in LT-photoluminescence (LT-PL) spectrum measured at 13 K (not shown).…”
Section: Representative Resultsmentioning
confidence: 67%
“…For the growth of ZnO-based heterostructures, however, more reports on the formation of 2DEG are realized by MBE at the present time prior to the commercialization of the potential applications 10 11 12 . Recently, we have developed MBE growth of high quality ZnO heterostructures with an accurate control of surface polarity on Ga-polar GaN templates 13 . It was found that with Zn pre-exposure treatment, ZnO layers so grown exhibited Zn-polarity when nucleated with low VI/II ratios (<1.5), while those nucleated with VI/II ratios above 1.5 exhibited O-polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental Procedures : Zn‐polar Be 0.02 Mg 0.26 ZnO/ZnO heterostructures were grown by plasma‐enhanced molecular beam epitaxy (PE‐MBE) on GaN/sapphire templates that were prepared by metal‐organic chemical vapor deposition (MOCVD). Zn polarity was maintained by using a low VI/II ratio during the nucleation of ZnO at 300 °C on GaN . The thickness of the Be 0.02 Mg 0.26 ZnO barrier and the ZnO channel layer was 30 and 300 nm, respectively.…”
Section: Electron Mobilities Sheet Carrier Concentrations Schottky mentioning
confidence: 99%